2017
DOI: 10.1136/bmjqs-2016-006123
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a ‘Do not interrupt’ bundled intervention to reduce interruptions during medication administration: a cluster randomised controlled feasibility study

Abstract: AimTo evaluate the effectiveness of a ‘Do not interrupt’ bundled intervention to reduce non-medication-related interruptions to nurses during medication administration.MethodsA parallel eight cluster randomised controlled study was conducted in a major teaching hospital in Adelaide, Australia. Four wards were randomised to the intervention which comprised wearing a vest when administering medications; strategies for diverting interruptions; clinician and patient education; and reminders. Control wards were bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 27 publications
3
87
1
3
Order By: Relevance
“…Similar to the findings from the study done in hospitals affiliated with Mashhad university of medical sciences in, Mashhad, Iran with the purpose of evaluating the medication errors among 530 nurses. 31 Another study with similar findings was conducted in Saudi Arabia and showed that 30.9% responded that the most common medication administration error is the wrong timing of medication administration. 32 Moreover, using the documentation of Pediatric mediation administration errors in Canadian pediatric center wrong time error accounted 168 cases (45.2%) among 272 cases.…”
Section: Types Of Maesmentioning
confidence: 66%
“…Similar to the findings from the study done in hospitals affiliated with Mashhad university of medical sciences in, Mashhad, Iran with the purpose of evaluating the medication errors among 530 nurses. 31 Another study with similar findings was conducted in Saudi Arabia and showed that 30.9% responded that the most common medication administration error is the wrong timing of medication administration. 32 Moreover, using the documentation of Pediatric mediation administration errors in Canadian pediatric center wrong time error accounted 168 cases (45.2%) among 272 cases.…”
Section: Types Of Maesmentioning
confidence: 66%
“…In this issue of BMJ Quality and Safety , Westbrook7 and colleagues report a cluster randomised controlled trial of a bundled intervention to reduce interruptions during medication administration in a hospital using paper-based prescribing. This well-designed feasibility study tested a bundled intervention based on ‘Do Not Disturb’ vests and the education of healthcare professionals, patients and visitors.…”
mentioning
confidence: 99%
“…Taking into account these points, together with the findings of the study by Westbrook et al ,7 we therefore need to consider whether other interventions may be more appropriate, and, if so, which. Interventions may relate to reducing the risk from interruptions or to other unrelated aspects of medication administration.…”
mentioning
confidence: 99%
“…Consider a second example, in which Westbrook and colleagues evaluated a bundled intervention to reduce nurse interruptions during medication administration using a cluster randomised controlled trial (RCT) 13. For every 100 medication administrations, nurses on intervention wards experienced 15 fewer non-medication-related interruptions compared with control wards.…”
Section: Two Recent Examples Of Improvement Interventions Evaluated Umentioning
confidence: 99%
“…Consequently, it made sense to randomise wards to a fixed intervention or to usual care and focus on evaluating the impact. That said, it obviously occurred to Westbrook et al 13 that the nurses might not like wearing the vests, since they solicited this feedback as part of their results. Thus, they might have anticipated the need for making some changes to the intervention.…”
Section: Why These Two Examples?mentioning
confidence: 99%